(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2022)
Si ricordano le iscrizioni pubblicate per merito di Henri Treziny e si ripercorre la bibliografia su due nomi personali, l’unico femminile noto a Megara Iblea e il secondo inesistente. The inscriptions published thanks to Henri Tréziny are remembered, and two personal names are used to retrace the bibliography: the first being the only female known in Mégara Hyblaea and the second non-existent.